2003
DOI: 10.1037/0097-7403.29.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Temporally massed CS presentations generate more fear extinction than spaced presentations.

Abstract: Rodent fear conditioning models both excitatory learning and the pathogenesis of human anxiety, whereas extinction of conditional fear is a paradigm of inhibitory learning and the explicit model for behavior therapy. Many studies support a general learning rule for acquisition: Temporally spaced training is more effective than massed training. The authors asked whether this rule applies to extinction of conditional fear in mice. The authors find that both short- and long-term fear extinction are greater with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(143 citation statements)
references
References 57 publications
10
130
3
Order By: Relevance
“…It is worth noting that during long extinction sessions, neither learning condition ( Figs 7A,B, 8A) showed a complete reduction in levels of CR. This is consistent with other studies using single-session extinction in rodents (Cain et al 2003) and humans (Tsao and Craske 2000). It is unclear whether the reduction of fear during extinction predicts fear expressed during subsequent tests (for review, see Craske et al 2014).…”
Section: Methodssupporting
confidence: 80%
“…It is worth noting that during long extinction sessions, neither learning condition ( Figs 7A,B, 8A) showed a complete reduction in levels of CR. This is consistent with other studies using single-session extinction in rodents (Cain et al 2003) and humans (Tsao and Craske 2000). It is unclear whether the reduction of fear during extinction predicts fear expressed during subsequent tests (for review, see Craske et al 2014).…”
Section: Methodssupporting
confidence: 80%
“…Additionally or alternatively, the improvement in this subgroup might not necessarily result from the added exposure but rather from the spacing of the additional exposure sessions during the booster phase. Animal studies (see Fitzgerald et al, 2014) showed that, once initiated in a massed way, extinction learning is boosted when subsequent trials are spaced (Cain et al, 2003). Third, the patients in this cluster may have needed exposure in a variety of contexts such as the home environment.…”
Section: Discussionmentioning
confidence: 99%
“…More theoretically, results from animal studies about fear extinction learning (i.e. the development of new associations with the stimulus that inhibits the manifestation of the original fear memory and the presumed mechanism of action of exposure therapy; see for an overview Fitzgerald, Seemann, & Maren, 2014) showed that once extinction learning is initiated in a massed way, further extinction learning is more effective when trials are spaced (Cain, Blouin, & Barad, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…This study follows from a previous report from this group suggesting that extinction, unlike acquisition, proceeds more readily with massed trials (6 s interstimulus interval or ISI) than with spaced trials (600 s ISI), even when total CS exposure is held constant. 269 Massed extinction training produced a robust within-session decline in freezing that was maintained in a later retention test, whereas spaced extinction training maintained or even increased freezing during nonreinforced CS presentations and in a subsequent retention test, an effect that these authors attributed to 'incubation' of fear (cf. Berman et al 63 ).…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%